2021
DOI: 10.1051/0004-6361/202140508
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a directly imaged planet to the young solar analog YSES 2

Abstract: Context. To understand the origin and formation pathway of wide-orbit gas giant planets, it is necessary to expand the limited sample of these objects. The mass of exoplanets derived with spectrophotometry, however, varies strongly as a function of the age of the system and the mass of the primary star. Aims. By selecting stars with similar ages and masses, the Young Suns Exoplanet Survey (YSES) aims to detect and characterize planetary-mass companions to solar-type host stars in the Scorpius-Centaurus associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 146 publications
(175 reference statements)
1
15
0
Order By: Relevance
“…We also aim to discover additional planets and substellar companions whose orbits and atmospheres are accessible to direct characterization. Finally, the results of this survey will be directly comparable to the demographics of planets around A-stars in the closer (but slightly older) moving groups targeted largely by past surveys (e.g., Nielsen et al 2019;Vigan et al 2021), and also to lower-mass members of the Sco OB2 association (Bohn et al 2020(Bohn et al , 2021−enabling trends in exoplanet properties to be identified across host star age, mass, and formation environment.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…We also aim to discover additional planets and substellar companions whose orbits and atmospheres are accessible to direct characterization. Finally, the results of this survey will be directly comparable to the demographics of planets around A-stars in the closer (but slightly older) moving groups targeted largely by past surveys (e.g., Nielsen et al 2019;Vigan et al 2021), and also to lower-mass members of the Sco OB2 association (Bohn et al 2020(Bohn et al , 2021−enabling trends in exoplanet properties to be identified across host star age, mass, and formation environment.…”
Section: Introductionmentioning
confidence: 64%
“…Finally, our results offer a complementary sample to past studies that were largely focused on lower-mass stellar hosts in the solar neighborhood, and also to other ongoing surveys of both higher and lower-mass stars in Sco OB2. Taken in combination with GPIES (Nielsen et al 2019) and SHINE (Vigan et al 2021), the BEASTS survey of B-type stars (Janson et al 2021), and YSES survey (Bohn et al 2020(Bohn et al , 2021 of solar-type stars (both also focused on Sco OB2), these surveys provide a rich and comprehensive view of wide-orbit giant plants around nearby young stars. Together, they inform our understanding of exoplanet demographics, and perhaps of equal importance, enable the yield of future exoplanet imaging surveys to be enhanced by targeting stars around which detectable planets are more likely to exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2M0437b is much younger, and therefore likely to be significantly less massive than HIP 65426b. YSES-2b is a similar planet orbiting a member of the same association; it is less luminous than HIP 65426b, and thus predicted to be less massive (∼6M JUP , Bohn et al 2021). Other comparable objects include the four known planets (bcde) of the HR 8799 system.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…been discovered to date (e.g. Marois et al 2008Marois et al , 2010Lagrange et al 2010;Bohn et al 2020Bohn et al , 2021.…”
Section: Estimating Masses With Spectral Energy Distribution Analysismentioning
confidence: 99%